HEALTH EDUCATION IN ADOLESCENTS ABOUT HIV / AIDS IN SMKN 2 KOLAKA - Abd Gani Baeda; Evodius Nasus; Yuhanah; Heriviyatno Julika Siagian; Risqi Wahyu Susanti (LPPM STIKes MERCUBAKTIJAYA Padang, 2022)
Background : Indonesia is one of the countries with 50,282 HIV sufferers in 2019 and 7,036 AIDS sufferers, with 180 HIV cases reported in 2019 and 52 AIDS cases in Southeast Sulawesi. The purpose of this service activity is to prevent HIV / AIDS transmission through youth education for students of SMKN 2 Kolaka. Method : This service is a preventive measure by providing HIV/AIDS education to adolescents (students) on November 23, 2020 at SMKN 2 Kolaka Result: the participants who participated in this service were 35 youth education students who were very enthusiastic about receiving educational materials about HIV/AIDS with the results of this education increasing the knowledge of adolescent students of SMKN 2 Kolaka about HIV/AIDS.